INTERNATIONAL RELATIONS AS A FACTOR INFLUENCING ENTERPRISE PERSONNEL MANAGEMENT - SKLIARUK, Tetiana; DANYLIUK, Roman (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the main trends in the development of international relations that determine the current dynamics of global cooperation and competition. It analyzes the key challenges and opportunities faced by international actors in the context of economic, political, and sociocultural turbulence.Special attention is given to the issue of adapting human resource management systems to changes in the external environment. Globalization processes, technological progress, and economic challenges demand flexibility and innovative approaches in working with personnel. An important aspect is the consideration of mechanisms for improving human resource management efficiency through the integration of modern international standards, which enhances the competitiveness of companies in the global market.Moreover, the article analyzes the issue of adapting corporate culture to the international environment. The successful functioning of organizations in a cross-cultural space depends on their ability to implement effective communication methods, ensure openness, and harmonize internal values with global trends.Additionally, the effectiveness of using international standards in human resource management, such as ISO, ILO, and other regulatory acts, is considered. It is proven that their implementation contributes to improving the quality of labor relations, increasing the level of social responsibility in business, and strengthening trust between employees and employers.The results obtained can be useful for scholars, managers, international business experts, and human resource management professionals who aim to improve organizational performance in the face of global challenges.
Keywords: international relations; human resource management; corporate culture; adaptation; international standards; global market